2020
DOI: 10.1016/j.tranon.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Treatment for Diabetes Mellitus Correlates with Progression and Survival in Colorectal Carcinoma

Abstract: BACKGROUND: Diabetes mellitus is unfavorably associated with cancer risk. The purpose of this multidisciplinary project was to evaluate a possible association of diabetes mellitus and other comorbidities and their treatment with progression of colorectal cancer. PATIENTS AND METHODS: We investigated the correlation between pathological characteristics and clinical course, including comorbidities in 1004 Czech patients diagnosed and surgically treated for colorectal adenocarcinoma (CRC) between 1999 and 2016. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Data concerning potential uses of metformin as an adjuvant treatment in patients who have already developed colorectal cancer are even more scarce: while a series of published papers suggest that metformin use might be associated with improved survival [ 85 , 86 , 87 , 88 ], in all these studies, the number of patients with unresected metastatic disease is rather low (usually lower than 3–4% of the whole patient population).…”
Section: Resultsmentioning
confidence: 99%
“…Data concerning potential uses of metformin as an adjuvant treatment in patients who have already developed colorectal cancer are even more scarce: while a series of published papers suggest that metformin use might be associated with improved survival [ 85 , 86 , 87 , 88 ], in all these studies, the number of patients with unresected metastatic disease is rather low (usually lower than 3–4% of the whole patient population).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in cancer cells it has been demonstrated that metformin possess anti-tumorigenic properties and proven to inhibit cell proliferation, invasion and migration in most of the cancer cells. It appears to affect multiple key processes related to cell growth, proliferation, and survival [27][28][29][30]. To proceed with our hypothesis, Metformin, Vemurafenib and 5-Azacytidine were docked with TSHR protein using iGEMDock software to determine the docking scores in which the protein-ligand interaction were successful in identifying that the drugs were docked with TSHR with common binding site sharing between metformin and vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…However, to achieve and maintain specific glycemic targets, the majority of patients require glucose-lowering drugs. Metformin is currently the first-line and widely used pharmacological therapy for patients with T2DM because of its potential benefits, including cardioprotective effect, loss of weight, and prevention of some comorbid diseases 15 22 . If lifestyle interventions and a maximally tolerated dose of metformin fail to achieve the glycemic target within 3 months follow-up, the regimen would be changed to combination therapy 15 .…”
Section: Introductionmentioning
confidence: 99%